2017
DOI: 10.1159/000481772
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of NOTCH3 in Mouse Spermatogonia

Abstract: Stable and sustainable spermatogenesis is supported by the strict regulation of self-renewal and differentiation of spermatogonial stem cells (SSC), which are a rare population of undifferentiated spermatogonia. It has been revealed that some signaling factors regulate the self-renewal of SSC; however, the molecular mechanism of SSC maintenance is still not completely understood. Notch signaling is an evolutionarily conserved juxtacrine signaling that plays important roles in the cell fate determination of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…It is worth mentioning that in mouse HES1 was detected in spermatogonia of immature testis. In adult mice the expression in spermatogonia decreased and HES1 was detected mainly in Sertoli cells [9,15,48]. In pubertal rats we found the expression of this protein in both spermatogonia and Sertoli cells.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…It is worth mentioning that in mouse HES1 was detected in spermatogonia of immature testis. In adult mice the expression in spermatogonia decreased and HES1 was detected mainly in Sertoli cells [9,15,48]. In pubertal rats we found the expression of this protein in both spermatogonia and Sertoli cells.…”
Section: Discussionmentioning
confidence: 64%
“…Nevertheless, the presence of N1ICD and N2ICD and Notch effector genes in spermatogonia strongly suggest that Notch pathway is involved in the control of these cells. In addition, Okada et al [15] showed the expression of cleaved form of Notch3 receptor (N3ICD) and HES1 in prepubertal and adult mouse spermatogonia. Altogether, Notch signaling is clearly activated in spermatogonia via different Notch receptors, but whether each of them play specific role or they are functionally redundant remains to be explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During postnatal development and along the spermatogenic cycle of adult male mouse, three Notch receptors (Notch 1-3) and ligands (Delta-like 1, 4 and Jagged 1, 2) were identified in the testis (Mori et al, 2003;Garcia & Hofmann, 2013;Murta et al, 2013;Okada et al, 2017;Kami nska et al, 2018). Although Notch receptors were identified both in germ and in Sertoli cells, Notch 1 signaling in adult seminiferous tubules is activated predominantly in Sertoli cells (Garcia & Hofmann, 2013;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, NFYA is overexpressed in some cancers and its motif is related to meiosis-specific gene regulation [56][57][58] . Hes1 is expressed in prepubertal spermatogonia in mouse and SSEA+ human SSCs [59,60] . It can also promote EMT via the AKT pathway in cancers [61] .…”
Section: Dynamic Changes In Accessibility Of Regulatory Elements and mentioning
confidence: 99%